Advanced Pulmonary and Cardiac Support of COVID-19 Patients: Emerging Recommendations From ASAIO—a Living Working Document. (May 2020) - Rajagopal, Keshava; Keller, Steven P.; Akkanti, Bindu; Bime, Christian; Loyalka, Pranav; Cheema, Faisal H.; Zwischenberger, Joseph B.; El Banayosy, Aly; Pappalardo, Federico; Slaughter, Mark S.; Slepian, Marvin J.
Abstract : The severe acute respiratory syndrome-CoV-2 is an emerging viral pathogen responsible for the global coronavirus disease 2019 pandemic resulting in significant human morbidity and mortality. Based on preliminary clinical reports, hypoxic respiratory failure complicated by acute respiratory distress syndrome is the leading cause of death. Further, septic shock, late-onset cardiac dysfunction, and multiorgan system failure are also described as contributors to overall mortality. Although extracorporeal membrane oxygenation and other modalities of mechanical cardiopulmonary support are increasingly being utilized in the treatment of respiratory and circulatory failure refractory to conventional management, their role and efficacy as support modalities in the present pandemic are unclear. We review the rapidly changing epidemiology, pathophysiology, emerging therapy, and clinical outcomes of coronavirus disease 2019; and based on these data and previous experience with artificial cardiopulmonary support strategies, particularly in the setting of infectious diseases, provide consensus recommendations from American Society for Artificial Internal Organs. Of note, this is a living document, which will be updated periodically, as additional information and understanding emerges.